Regional Relationships in New Housing Prices in Colombia (2015)
This study examines the regional relationships in the price of new housing in seven major cities in Colombia during the period 1999 Q2 to 2013 Q3 using time series statistical techniques -- We show that while regional prices tend to converge in the long run, there is no evidence that price shocks in the capital (Bogotá) diffuse to other cities -- We do find evidence that prices in some smaller cities are affected by prices in neighboring cities